Stress corrosion cracking failure of friction stir welded nuclear grade austenitic stainless steel. (February 2021) - Rajasekaran, R.; Lakshminarayanan, A.K.; Damodaram, R.; Balasubramanian, V.
Highlights: Defect free joint was produced on 316LN grade stainless steel using FSW process. SCC resistance of welds were evaluated in a boiling MgCl2 environment. Both the base metal and FSW joint displayed transgranular brittle mode of failure. At lower stress levels, the fraction location was at the center of the stir zone. At higher stress levels, the fracture location was migrated to the retreating side. Higher crack propagation was observed at TMAZ-retreating side of the FSW joint. Abstract: Stress Corrosion Cracking behavior of Austenitic Stainless Steels (SS) in a chloride environment has been investigated by several methods. In this investigation failure of emerging structural material for nuclear reactor (316LN grade austenitic stainless steel) and its Friction Stir Welded (FSW) joint due to stress corrosion cracking were analyzed in a chloride environment. FSW joint was fabricated between 316LN plates with optimized process parameters. Initially, hardness and tensile properties were analyzed across the weld zone to evaluate the mechanical properties of the welded joint. Microstructural characterization of base metal (BM) and weld zone were done by Optical Microscope (OM), and Scanning Electron Microscope (SEM). Grain boundary analysis was done by Transmission Electron Microscope (TEM). Microstructural evolution revealed that the FSW process is capable to refine and reduce grain size nearby 12 times that of the base metal by Continuous Dynamic Recrystallization mechanism (CDRX). Improved strength and hardness are also recorded at the weld zone compared to the base metal. Boiling 45 wt% MgCl2 solution at constant load condition as per ASTM standard G36 was used to assess SCC failure on base metal and FSW joint. Failure due to Chloride Stress Corrosion Cracking (CSCC) on weld samples were investigated and compared with its base metal samples at different tensile stress conditions (20%, 40%, 60%, 80%, 100% of base metal yield stress values). From the experimental result steady-state elongation rate ( I SS ), Transition time ( t ss ) and time to failure ( t f ) were evaluated and generalized equations to predict time to failure of base metal and FSW weldment was generated. The impact of microstructural morphology on SCC failure of the FSW joint was investigated. The fracture location of the weld joint, nature of crack advancement of both base metal and FSW joint was analyzed by the SEM study. A study of fracture surface displayed brittle nature transgranular failure for base metal as well as FSW samples.